Solve for y y/-2.6=3.2

Math
y-2.6=3.2
Multiply both sides of the equation by -2.6.
-2.6⋅y-2.6=-2.6⋅3.2
Simplify both sides of the equation.
Tap for more steps…
Simplify -2.6⋅y-2.6.
Tap for more steps…
Move the negative in front of the fraction.
-2.6⋅(-y2.6)=-2.6⋅3.2
Multiply by 1.
-2.6⋅(-1y2.6)=-2.6⋅3.2
Factor 2.6 out of 2.6.
-2.6⋅(-1y2.6(1))=-2.6⋅3.2
Separate fractions.
-2.6⋅(-(12.6⋅y1))=-2.6⋅3.2
Divide 1 by 2.6.
-2.6⋅(-(0.384615‾y1))=-2.6⋅3.2
Divide y by 1.
-2.6⋅(-(0.384615‾y))=-2.6⋅3.2
Multiply 0.384615‾ by -1.
-2.6⋅(-0.384615‾y)=-2.6⋅3.2
Multiply -2.6(-0.384615‾y).
Tap for more steps…
Multiply -0.384615‾ by -2.6.
1y=-2.6⋅3.2
Multiply y by 1.
y=-2.6⋅3.2
y=-2.6⋅3.2
y=-2.6⋅3.2
Multiply -2.6 by 3.2.
y=-8.32
y=-8.32
Solve for y y/-2.6=3.2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top